Mirzayev, Habib - (:unkn) unknown (My University, 2026)
Habib Adil oglu Mirzayev was born on 14 December 1961 in the Yardimli District, Republic of Azerbaijan. From 1968 to 1978, he completed his secondary education at Secondary School No. 1 named after M.F. Akhundov in Yardimli. In 1980, he entered the Faculty of Philology at Azerbaijan State Pedagogical University and graduated in 1984 with a degree in Teaching Azerbaijani Language and Literature. Since 1991, he has been employed at the Department of Azerbaijani Language and Pedagogy of Azerbaijan Technical University, where he worked as a Laboratory Assistant and later as a Senior Laboratory Assistant. In 1996, he was appointed Lecturer, and in 2003, he was promoted to Senior Lecturer. Since 2005, he has held the academic title of Associate Professor. Between 2006 and 2011, he simultaneously served as Vice Dean of the Faculty for the Education of Foreign Citizens and Deputy Head of the Department. In 2011, Dr. Mirzayev was elected Head of the Department of Azerbaijani Language and Pedagogy. In 2016, he was re-elected to the same position for a second term. Dr. Mirzayev holds a PhD in Philology and the academic title of Associate Professor. As a scholar specializing in philology, he carries out academic and pedagogical activities across all academic specializations offered at the University. He is the author of approximately 200 scientific publications and nine books.